Measurement of Effective Dose Detox for Workers Exposed to Benzene Toxins in Sidoarjo Paint Industry (Indian Journal of Forensic Medicine & Toxicology, 2020)
One of the aromatic hydrocarbon compounds, namely benzene. Benzene is a colorless liquid with a sweetodor (sweet odor), volatile in the air, soluble in water and flammable. Today the use of benzene used bythe paint manufacturing industry. However, the concentration of benzene that exceed standards requiredthreshold value will negatively impact the health of workers in Sidoarjo Paint Industry. Benzene can threatenthe safety and human health if inhaled because it can damage the blood forming system profile in humans.The purpose of this research is to reduce the exposure of benzene by determining the effective dose of toxindetox benzene in the paint industry, Sidoarjo, East Java. This study was an observational study with crosssectionalapproach.result the average concentration of benzene in the workplace respondents was 3.28 mg /m3. The average effective dose should be consumed by the respondent for the avocado intake is 0,011 mg /day, chicken intake 0,026 mg / day, intake of grapefruit 0.033 mg/day, and carrot intake was 0.063 mg /day.